Female impersonator wearing a Latin dancer costume. - Sahl, Ted (photographer):::Creator::::::::::::
Female impersonator wearing a Latin dancer costume with unattached ruffled sleeves. One hand is placed on the front of the thigh and the other hand is placed on the wall just above head height.